Bridging family boundaries: mediating postmodern complexity in urban Sinhalese Sri Lankan families. Issue 4 (4th July 2018) - Edirisingha, Prabash Aminda; Aitken, Robert; Ferguson, Shelagh
ABSTRACT: There is a bricolage of competing local and global ideologies, value systems, and practices vying for the attention of urban South Asian consumers. We term this as "postmodern complexity". Drawing from a three-year ethnographic research expedition on Sinhalese Sri Lankan families, we illustrate the process by which these families mediate postmodern complexity during new family formation. Our findings support an emergent framework to understand the processes in which families negotiate the influence of competing discourses and illustrate that the process is a perpetual experimentation spanning across three overlapping stages. We argue that negotiating postmodern complexity in our families is a hybrid and creolised resolution that is tailored to each family's unique identity needs. Families can draw from a multitude of meanings that are anchored in consumption in order to create a unique family identity that is most appropriate to their identity pursuits.